The relationship between Kolb\'s learning styles and intellectual preferences among students at Farhangian University of Kerman - hamidreza Arman; hamdollah manzari; amanollah soltani; zahra Zeinaddini Meymand (مجله علوم روانشناختی, 2019)
Background: The individual differences between learners in different dimensions and styles are factors influencing learning. Aims: The present study was conducted to investigate the relationship between Kolb's learning styles and intellectual preferences in the students of Kerman University of Medical Sciences in Kerman. Method: The design of the research is a correlation model. The statistical population of this study was all female and male students of Farhangian University of Kerman province. The sample size was 346 students (238 males and 108 females) who were selected by stratified sampling method. The research tools were Kolb's Learning Style Questionnaire (1985) and Nadoraman's (1960) Preference Questionnaire. Data were analyzed using statistical methods such as frequency, mean, standard deviation and Pearson correlation coefficient. Results: The results showed a positive and significant relationship between abstract conceptualization style with A quadrant and D quarter, and positive and meaningful with mean C quarter, but not significant with quarter B. The relationship between the style of experiential experience with strong, positive, and meaningful C quadrants is positive and meaningful with the medium of D quarter. But with quarter B and quarter A it is not meaningful. The relationship between the observational view style and the A quarter is A, strong, positive and significant, with a quarter B and a moderate C quarter, is positive and significant, but not significant with D quarter(P<0.01). Conclusions: So recognize to learning styles and intellectual preferences in students can achives academic achievement.